The allocation of carbohydrates from vegetable raw materials and their identification with the use of capillary electrophoresis - Stanislav I. Biryulin; Nataliya E. Posokina; Marina V. Trishkaneva (Овощи России)
Relevance. Carbohydrates are integral components of the cells and tissues of all living organisms of the plant and animal world; they are important components of the plant cell walls, as well as the extracellular matrix of animal and human tissues. The type of monosaccharide composition of polysaccharides determines their biological functions for the organism. However, it is difficult to establish the relationship between the structure of the carbohydrate molecule and its biological function.Methods. In this article, the author provides an overview of methods for identifying the monosaccharide composition of plant polymers by capillary electrophoresis, in order to optimize the sample preparation procedure and the conditions of analysis. A scheme for the stepwise release of polysaccharides from raw materials is given: the isolation of soluble monosaccharides and polysaccharides, the extraction of the pectin fraction, the extraction of cellulose and hemicelluloses, in order to study the composition of each fraction. A procedure for acid hydrolysis of polymers to monosaccharides using oxidizing agents such as sulfuric and trifluoroacetic acid is described. In the final part of the article, three different schemes for the identification of the monosaccharide composition were analyzed, namely, separation of the components under strongly alkaline conditions, preliminary derivatization with 1-phenyl-3-methyl-5-pyrazolone, preliminary preparation of (S) (-) α-methylbenzylamine S-PEA) derivatives.Results or Findings. An analysis of the literature shows that the composition of polysaccharides is widely studied by various methods. At the same time, a number of problems remain associated with the implementation of these methods in terms of sample preparation and identification of all monosaccharides characteristic of the studied raw materials. The method of capillary electrophoresis can solve some of these problems; however, little has been studied. The study of carbohydrates in plant objects begins with the procedure for extracting carbohydrates (polysaccharides and monosaccharides) from the plant matrix, hydrolysis of polysaccharides, and subsequent identification using the CE method. The optimization of this scheme of the CE method for determining the composition of polysaccharides is an urgent scientific task.